2013
DOI: 10.1016/j.jviromet.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Detection and differentiation of field and vaccine strains of canine distemper virus using reverse transcription followed by nested real time PCR (RT-nqPCR) and RFLP analysis

Abstract: Canine distemper virus (CDV) is the cause of a severe and highly contagious disease in dogs. Practical diagnosis of canine distemper based on clinical signs and laboratory tests are required to confirm CDV infection. The present study aimed to develop a molecular assay to detect and differentiate field and vaccine CDV strains. Reverse transcription followed by nested real time polymerase chain reaction (RT-nqPCR) was developed, which exhibited analytical specificity (all the samples from healthy dogs and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…In addition, affected by low abundance as whole urine, VEGF mRNA frequently found in tissues of renal cancer was at most detected in 62% (31/50) urine supernatant samples of patients with same disease . Some studies found a nested real time PCR method used in virus/bacteria detection could increase the clinical sensitivity . This, this study developed a nqPCR method by incorporating a conventional RT‐PCR for initial amplification of cf‐mRNAs in urine supernatant to improve the detection sensitivity and reduce false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, affected by low abundance as whole urine, VEGF mRNA frequently found in tissues of renal cancer was at most detected in 62% (31/50) urine supernatant samples of patients with same disease . Some studies found a nested real time PCR method used in virus/bacteria detection could increase the clinical sensitivity . This, this study developed a nqPCR method by incorporating a conventional RT‐PCR for initial amplification of cf‐mRNAs in urine supernatant to improve the detection sensitivity and reduce false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…Fischer et al [112] took it one step further by developing a technique of reverse transcription followed by a nested real-time PCR. The technique was performed on several clinical samples and proved to be two orders of magnitude more sensitive than RT-PCR.…”
Section: Molecular Assaysmentioning
confidence: 99%
“…Diagnosis is made by demonstration of typical histopathological lesions including the presence of viral inclusion bodies in lymphoid tissue, respiratory, urinary and gastro-intestinal tract epithelium and brain; by the presence of distinctive virions in negatively stained electron-microscopic preparations of faeces; and through the detection of viral antigen in tissue by immunofluorescence or immunohistochemistry [54,104]. Immunofluorescence has routinely been used as a diagnostic test; however, it is not sensitive and can detect CDV antigens only when the virus is still present in the epithelial cells [55,107] with false-negative results under certain clinical conditions [112,123].…”
Section: Pathological Examinationmentioning
confidence: 99%
“…RT-qPCR assays have been applied to detect and quantify canine distemper virus in clinical specimens of naturally infected dogs or to distinguish vaccine strains from wild strains, using two-step and real-time probes chemistry (ELIA et al, 2006;SCAGLIARINI et al, 2007;FISCHER et al, 2013;WILkES et al, 2014). Recently, surface plasmon resonance (SPR), electrochemical impedance spectroscopy (EIS) and conjugated gold nanoparticles methodologies were also developed for CDV detection (BASSO et al, 2013;2015a;2015b).…”
Section: Introductionmentioning
confidence: 99%